Impact of Tourism on Sustainable Development of Rural Areas: International Experience - GERMANOVICH, Aleksey Grigorievich; VASILIEVA, O. N.; ORDYNSKAYA, Marina Evgenievna; ALLANINA, Liliya Mansurovna; GOROKHOVA, Anna Evgenievna (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020, 2020)
Elimination of disproportions in the economic development of the country's regions and their transition to sustainable development is one of the priorities of Russian economic policy. This can be achieved by active search for the most effective directions of territorial development, actions aimed to form a positive image, and stimulation of profitable sectors of the economy. Tourism is one of the most effective directions for sustainable development of a territory. The article analyzes the scientific literature related to the problem of the connection between sustainable development of rural territories and rural tourism. The main rural tourism factors contributing to sustainable rural development and synergy effects from rural tourism have been identified based on an expert survey. Cases demonstrating the synergy effects of rural tourism are presented using the case method.